Facial edema associated to central vein stenosis in a chronic kidney disease patient - Linhares, Rafaela Jucá; de Araújo Júnior, Darlan Alves; Athayde Lima, Rafael Siqueira (Journal of Health & Biological Sciences, 2024)
Introduction: central vein stenosis (CVS) is a common complication in chronic kidney disease (CKD) patients, leading to vascular complications and higher mortality. Exposure to catheters is an important risk factor, and there is a wide spectrum of clinical presentation, including edema of the upper arm, neck, upper chest, and face, impairment of dialysis efficiency, and reduction of vascular accesses. Case report: a 41-year-old woman with CKD on dialysis and a history of multiple vascular accesses was admitted with a 3-month history of cervical and left hemiface edema. An angiotomography revealed marked stenosis in the proximal segment of the left brachiocephalic vein, and a venography confirmed the diagnosis of CVS, with subocclusive stenosis of the venous trunk and significant collateral veins. An endovascular treatment was performed with balloon angioplasty. She presented considerable improvement in the edema after the procedure. Conclusion: to avoid the development of central vein obstruction, it is important to enhance our knowledge about the main risk factors associated with this pathology. Although it is a treatable condition, recurrence of symptoms may occur, and subsequent vascular interventions may be needed. Therefore, prevention strategies are the most efficient approach.